1986
DOI: 10.1113/jphysiol.1986.sp016239
|View full text |Cite
|
Sign up to set email alerts
|

The influence of intestinal infusion of fats on small intestinal motility and digesta transit in pigs.

Abstract: SUMMARY1. The influence of duodenal and ileal infusion of nutrients on small intestinal transit of digesta, measured by the passage of phenol red marker, was studied in twelve pigs fitted with duodenal and ileal catheters, and a terminal ileal cannula.2. Changes in gastrointestinal motility were observed by electromyography and by use of an X-ray image intensifier in four of the pigs fitted additionally with nichrome wire electrodes in the gut wall and in seven pigs fitted only with a gastric catheter.3. Small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 13 publications
0
10
1
Order By: Relevance
“…This hypothesis is based on the assumption that the time required for protein digestion is a limiting factor. However, it has been shown that infusion of fat into the duodenum of pigs accelerates intestinal digesta transit (Gregory et al, 1986). Dietary fat has a depressing effect on the intestinal microflora, especially in the hind-gut, which is indicated in the present study by slightly lower methane production at the highest rapeseed oil level (Table 3).…”
Section: Digestibility Protein and Fat Balancementioning
confidence: 41%
“…This hypothesis is based on the assumption that the time required for protein digestion is a limiting factor. However, it has been shown that infusion of fat into the duodenum of pigs accelerates intestinal digesta transit (Gregory et al, 1986). Dietary fat has a depressing effect on the intestinal microflora, especially in the hind-gut, which is indicated in the present study by slightly lower methane production at the highest rapeseed oil level (Table 3).…”
Section: Digestibility Protein and Fat Balancementioning
confidence: 41%
“…This contrasts with findings in man where ileal infusion of undigested fat inhibited intake in excess of the level of energy infused (Welch et al 1985), perhaps via activation of an 'ileal brake', a slowing ofdigesta transit through the small intestine and slowing of gastric emptying (Read, McFarlane, Kinsman, Bates, Blackhall, Farrar, Hall, Moss, Morris, O'Neill, Welch, Lee & Bloom, 1984;Welch et al 1985). An 'ileal brake' mechanism appears to be absent in the pig, for ileal infusion of undigested fat or fat digestion products accelerates rather than slows transit through the small intestine (Gregory, Rayner & Wenham, 1986). This might explain why no immediate inhibition of food intake was seen in the present study.…”
Section: Inhibition Of Food Intake By Fats In the Pigmentioning
confidence: 49%
“…In adult pigs, however, the MMC is interrupted when the animal is fed discrete, large meals, but not by ad libitum feeding with the same diet (Bueno and Ruckebusch, 1976). Other research has shown that the caloric load regulates the characteristics of the amplitude of contraction and the duration of the intestinal postprandial pattern in adult pigs (Gregory et al, 1986), dogs (Schang et al, 1978;Schmid et al, 1992) as well as in adult humans (Schönfeld et al, 1998). Furthermore, it was demonstrated in adult dogs that during enteral infusion of low caloric load, MMC persisted, apart from a lengthening of phase II and resulting increase in duration of the MMC cycles; only higher caloric load caused complete disruption of the MMC and appearance of postprandial pattern (Defilippi, 2003).…”
Section: Introductionmentioning
confidence: 99%